Treatment outcomes among HIV-positive adolescents initiated on antiretroviral therapy in Sedibeng district, Gauteng - Kalonji-Makaloni, Njiba (My University, 2022)
Background: Initiation and adherence to antiretroviral therapy (ART) for people who tested positive for HIV have been shown to achieve virologic control, restore immunity, and reduce the risk of transmission of new infections. Understanding the impact of long-term ART outcomes could improve targeted intervention strategies to achieve among others viral suppression and retention in care. Studies have shown that adolescents have poor treatment outcomes compared to children and adults. Objective: To assess treatment outcomes among HIV-positive adolescents on ART in Sedibeng Health District, Gauteng province. Methods: The present study is a cross sectional study involving adolescents initiated on ART between 2010 and 2015. Patients’ clinical and treatment monitoring data were imported from the Tier.Net Software into STATA version 14 for analysis. The sample was divided into two adolescents’ groups: younger and older, aged 10-14 and 15-19 years, respectively. The main outcome measures included CD4+ count and HIV viral load at initiation and 6, 12, 24, 36, 48 and 60 months on ART. Other outcomes of analysis included the proportions of patients remaining in care, lost to follow-up (LTFU), transferred out and dead at these intervals. Results: Of the 254 participants, 173 (68.1%) were females, 180 (79.1%) were initiated in primary care (PHC) clinics and 74 (20.1%) in hospitals. A total of 132 (52%) participants were retained in care/ treatment at 60 months of ART. Of the 122 participants that were no longer in the treatment program, 65 (25.6%) were LTFU, 45 (17.7%) transferred out, and 12 (4.7%) had died. Participants who had lower median CD4 count at baseline were more likely to die (p= 0.049). The median baseline CD4 count was 135 cells mm-3 (IQR: 32-232) and substantially increased to 483.5 (IQR: 272-680) at the end of the 60 months period (p <0.001). At six months post initiation ART, 83(67.4%) out of 123 viral loads done were below 1000 copies/mL, among them only 26 (21.1%) were virally suppressed (<50 copies/mL). At twelve months the number of viral loads below 1000 copies/mL increased to 73.3% of sample taken. Viral rebounds were noted at 36 months. Younger females recorded a median viral load of 491.5 copies/mL (IQR: 107.5-16188) compared to males’ counterpart 152.5 copies/mL (IQR: 40-22157). As for old adolescents, males had higher rebound median viral load 1013.5 (IQR: 178.5-12084) compared to females 168 copies/mL (IQR: 124-1246), however, the difference between all the groups was not statistically significant (p 0.934). Females were more likely to have viral load <1000 copies/mL at 60 months (p 0.047). Compared to those initiated at PHC clinics, viral suppression was two times more likely to occur in participants initiated in the hospitals (HR 2.01: 95%CI 1.12-3.61; p 0.019). Younger adolescents had a 6.11 increased risk of experiencing virologic failure compared to older adolescents (p 0.033). Participants with an initial low CD4 count had a 3.19 Hazard Ratio (HR) of virologic failure compared to those who were put on treatment with a high CD4 count (p 0.035). Conclusion: This study shows that adolescents continue to experience challenges with ART. Except for CD4 count, the study showed a prevalent trend of poor treatment outcomes including poor viral load suppression and low rates of retention in care. The resurgence in high viral load after 12 months that peaks at 36 months, also underscores the need for ongoing clinician’s adherence to the virological monitoring guidelines, and the provision of support for patients to adhere to ART treatment. The findings from this cohort are important for the planning and implementation of HIV services corresponding to the needs of adolescent population in Sedibeng district. Youth-friendly services including outreach for holistic management of HIV-positive adolescents is recommended for implementation in all health facilities.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Public Health in Maternal and Child Health to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2022